From Copyright Cartels to Commons and Care: A Public Infrastructure Model for Canadian Music Communities - Selman, Brianne; Fauteux, Brian; deWaard, Andrew (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2022)
Using research on the political economy of the music industries, interviews with independent musicians about their lived experiences, and the authors' experience participating in government copyright consultations in Canada, this article discusses how the market power of major music companies, and their capture of the policy-making process through lobbying, has made copyright reform an extremely limited avenue for remedying the variety of hardships facing musicians in the streaming media era. Against the continued consolidation and concentration of power within the music industries, we explore a case study of Edmonton Public Library’s Capital City Records as an alternative model that may inspire further initiatives that advocate for artists and users. We conclude by discussing a commons-based, public infrastructure and governance model that could serve as a tool to circumvent uneven power dynamics in the music industries, facilitate stronger music communities, and provide sustainable livelihoods for working musicians in Canada.